La Frontera : Forests and Ecological Conflict in Chile's Frontier Territory - Klubock, Thomas Miller (Book collections on Project MUSE., 2014)
In La Frontera, Thomas Miller Klubock offers a pioneering social and environmental history of southern Chile, exploring the origins of today's forestry ""miracle"" in Chile. Although Chile's forestry boom is often attributed to the free-market policies of the Pinochet dictatorship, La Frontera shows that forestry development began in the early twentieth century when Chilean governments turned to forestry science and plantations of the North American Monterey pine to establish their governance of the frontier's natural and social worlds. Klubock demonstrates that modern conservationist policies and scientific forestry drove the enclosure of frontier commons occupied by indigenous and non-indigenous peasants who were defined as a threat to both native forests and tree plantations